MicroRNA-937 is overexpressed and predicts poor prognosis in patients with colon cancer - Liu, Huiya (Diagn Pathol, 2019)
BACKGROUND: Colon cancer is a heterogeneous tumor and a leading cause of cancer-related mortality. MicroRNA (miRNA) has been proposed as the biomarker in cancers. The aim of this study was to investigate the clinical significance and potential functional role of miR-937 in colon cancer. METHODS: In the present study, reverse transcription-quantitative polymerase chain reaction (qRT-PCR) was conducted to examine the expression levels of miR-937 in colon cancer tissues and cell lines. Kaplan-Meier curve and Cox regression analyses were used to determine the prognostic impact of miR-937 on survival. Cell Counting Kit-8 and Transwell assays were performed to examine cell proliferation, migration, and invasion, respectively. RESULTS: miR-937 was significantly upregulated in colon cancer tissues and cell lines. Clinical analysis results showed that miR-937 expression was associated with lymph node metastasis and TNM stage. Patients with high miR-937 expression predicted a shorter overall survival rate. Functionally, overexpression of miR-937 promoted cell proliferation, migration, and invasion, while inhibition of miR-937 inhibited these cellular behaviors in vitro. CONCLUSIONS: These results suggested that miR-937 may act as a prognostic biomarker and a potential target for therapeutic strategy, as well as promote proliferation, migration, and invasion of colon cancer.